h-25=2h-8

Simple and best practice solution for h-25=2h-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h-25=2h-8 equation:


Simplifying
h + -25 = 2h + -8

Reorder the terms:
-25 + h = 2h + -8

Reorder the terms:
-25 + h = -8 + 2h

Solving
-25 + h = -8 + 2h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-2h' to each side of the equation.
-25 + h + -2h = -8 + 2h + -2h

Combine like terms: h + -2h = -1h
-25 + -1h = -8 + 2h + -2h

Combine like terms: 2h + -2h = 0
-25 + -1h = -8 + 0
-25 + -1h = -8

Add '25' to each side of the equation.
-25 + 25 + -1h = -8 + 25

Combine like terms: -25 + 25 = 0
0 + -1h = -8 + 25
-1h = -8 + 25

Combine like terms: -8 + 25 = 17
-1h = 17

Divide each side by '-1'.
h = -17

Simplifying
h = -17

See similar equations:

| m-1=96 | | 8(-8x-6)=6x-22 | | 2n+n-6=30 | | -4=(v+1) | | -34=8u+2(u+7) | | 1.9(1.6+3.7)= | | 2(x*7)=5(x-7) | | 5(z-1)=(4z+4) | | (x-3)=(6x-2) | | X+11x-2=0 | | 2(x-2)+14=10x+5-4x | | 36x^2+25=60 | | 7=(-5v-8) | | 4x+3+5x=3x-9 | | 6x-(2x-1)=9x+(2-x) | | -3[x+4]=12 | | 2x-3+19=180 | | -2[2x-3]=26 | | 6v=(2v+3) | | 16x^2-48x=0 | | 0.9x-1.1=0.3+.2x | | 4y+8+2y=20 | | 5[y-1]=40 | | 2y-8=y-1 | | 6x^2+49x+90=2 | | 2(w-7)+2=-3(w-1) | | 4y+8+2y=18 | | 8[-a+2]=32 | | -3x-15=2x+5 | | 2*-4+6y=-12 | | 4y+4+3x=15 | | 0.5x-4=0.8-075x |

Equations solver categories